Ustalone Naprężenia Cieplne w Płytach - W. Nowacki (Engineering Transactions, 1959)
A proposed method for determining the stresses in a plate of moderate thickness in a temperature field, using the Green's function of the differential equation of the problem. For a number of simple cases such as that of infinite plate, plate strip, plate wedge etc., bending moments and torques are determined for a continuous and discontinuous temperature field. Finally, thermal stresses are discussed for a few cases of plates resting on an elastic foundation.